2018
DOI: 10.48550/arxiv.1810.07519
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contraction of cold neutron star due to in the presence a quark core

B. Eslam Panah,
T. Yazdizadeh,
G. H. Bordbar

Abstract: Motivated by importance of the existence of quark matter on structure of neutron star. For this purpose, we use a suitable equation of state (EoS) which include three different parts: i) a layer of hadronic matter, ii) a mixed phase of quarks and hadrons, and, iii) a strange quark matter in the core. For this system, in order to do more investigation of the EoS, we evaluate energy, Le Chatelier's principle and stability conditions. Our results show that the EoS satisfies these conditions. Considering this EoS,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…The obtained results in ref. [75], showed that, the existence of quark matter at center of neutron stars (or hybrid neutron stars) led to unstable against the radial adiabatic infinitesimal perturbations, while by applying the effect of cosmological constant to these stars, the dynamically stability keeps inside it.…”
Section: Dynamical Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results in ref. [75], showed that, the existence of quark matter at center of neutron stars (or hybrid neutron stars) led to unstable against the radial adiabatic infinitesimal perturbations, while by applying the effect of cosmological constant to these stars, the dynamically stability keeps inside it.…”
Section: Dynamical Stabilitymentioning
confidence: 99%
“…It is worthwhile that energy conditions (the null energy condition, weak energy condition, strong energy condition and dominant energy condition at the center of neutron star), stability and Le Chatelier's principle of this EoS have been investigated in ref. [75].…”
Section: Introductionmentioning
confidence: 99%